Strategi Pembelajaran Adaptif untuk Meningkatkan Keterampilan Menulis Berbasis AI - Nonny Rulisty Putri Sutikno; Umi Sri Wulan (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2025)
This research aims to examine the application of adaptive learning based on artificial intelligence (AI) in improving writing skills. The method used is a conceptual approach by conducting a literature review from various credible sources such as scientific journals, textbooks, and research reports related to learning to write, challenges faced by students, and the potential of AI in education. The analysis was conducted to understand how AI technology can provide feedback, adjust the difficulty level of the material, and improve students' writing skills. Research shows that AI-based adaptive learning can help students master writing skills more quickly. Through instant responses, materials tailored to their abilities, and relevant exercises, students can learn more effectively. AI also makes it easier for teachers to monitor student progress in more detail. However, no matter how sophisticated this technology is, the role of teachers remains irreplaceable. Teachers not only integrate AI into learning, but also provide guidance and emotional support that only humans can provide.